(untitled) (Innovaciones Educativas, 2020)
The pandemic caused by the virus responsible for COVID-19 has put educational systems around the world in check. Its unpredictable nature implied that virtual solutions had to be embraced in order to overcome moments of complete lockdown. This situation has evidenced all the different problems that afflict education and that these cannot be solved with the adopted emergency solutions. These are times to make the best of this crisis to reformulate many of the aspects of nowadays education systems to make them better and transform them if similar threats happen again. For this, technology must be an ally. This article reflects the need to design hybrid educational models that allow a fluent transition between face-to-face moments and virtual moments, especially if they are not programmed. Besides, a comprehensive vision of the school is necessary, including analog and digital contexts, suitable leadership for the digital age we are living in, and initial teacher training in the above-mentioned contexts.